Tracking Couples who leave the Study Location in Historical Studies of Fertility: an Australian Example - Moyle, Helen (Historical Life Course Studies, 2016)
The paper describes the methods used to create a database to study the fall of fertility in Tasmania, a colony of Australia, in the late 19th and early 20th centuries. The database was initially created from digitised Tasmanian vital registration data using techniques of family reconstitution. However, because of the high mobility in Australia in the 19th and early 20th centuries, couples who moved out of the colony were tracked to other places, and births and deaths that took place in other Australian colonies and other countries, such as New Zealand and England, were included in the database. A wide variety of data sources were used for this task, most of which are available on the internet. The results presented in the paper show that including families who moved outside Tasmania, either temporarily or permanently, produced a database that was more representative of the study population and provided more accurate birth histories for couples who at first glance appeared to have spent their married lives within the colony.